Android application modularization estimating model - Dvukhhlavov, Dmytro Eduardovych; Pelypets, Olha Serhiivna; Dvukhhlavova, Alona Serhiivna (Національний технічний університет "Харківський політехнічний інститут", 2025)
The relevance of the research, the results of which are presented, is determined by the fact that mobile applications have evolved into complex software systems with growing code bases, which complicates development, testing and support. It is shown that improving the maintainability and scalability of Android applications projects is possible by moving from a monolithic architecture to a modular architecture, based either on the list of functions that the application should perform, or on the architectural features of creating the application. To select a modularization option, a classification of approaches to modularization implementing is proposed. Regardless of which direction of modularization implement ing is chosen, it is aimed at reducing the impact of changes in one module on the need to make changes to others. Such a dependence between modules can be assessed by determining the cohesion and coherence of the project and individual modules. To quantitatively assess the advantages of modularization, a mathematical model has been developed that takes into account the balance between the cohesion of modules and the integrity of the project in whole. The model proposes to take into account the number of modules into which the monolithic architecture will be divided, the lev el of interaction between the modules that will be selected, as well as the level of their dependence on each other. Expressions are presented for automating calculations of division options into modules. The results of the assessment of the modularization of the Android application project for e-commerce based on different approaches to modularization implementing are presented. The obtained evaluation data allowed us to demonstrate the potential of modularization in reducing project assembly time, minimizing conflicts, and increasing project flexibility, offering a scalable solution for modern mobile development. Актуальність дослідження, результати якого представлені, визначається тим, що мобільні застосунки еволюціонували в складні програмні системи зі зростаючими кодовими базами, що ускладнює розробку, тестування та підтримку. Показано, що покращення супроводжуваності та масштабованості проєктів Android-застосунків можливе шляхом переходу від монолітної архітектури до модульної архітектури, виходячи або з переліку функцій, які має виконувати застосунок, або з архітектурних особливостей створення застосунку. Для вибору варіанта модуляризації запропоновано класифікацію підходів до модуляризації. Незалежно від того, який напрямок реалізації модуляризаці ї обрано, він спрямований на зменшення впливу змін в одному модулі на необхідність внесення змін до інших. Таку залежність між модулями можна оцінити, визначивши зв'язність та узгодженість проекту та окремих модулів. Для кількісної оцінки переваг модульності розроблено математичну модель, яка враховує баланс між зв'язністю модулів та цілісністю проєкту в цілому. Модель пропонує враховувати кількість модулів, на які буде розділена монолітна архітектура, рівень взаємодії між модулями, що будуть обрані, а також рівень їх зале жності один від одного. Представлено вирази для автоматизації розрахунків варіантів поділу на модулі. Представлено результати оцінки модуляризації проекту Android-застосунку для електронної комерції на основі різних підходів до реалізації модуляризації. Отримані оцінки дозволили продемонструвати потенціал модуляризації у скороченні часу збирання проекту, мінімізації конфліктів та підвищенні гнучкості проекту, пропонуючи масштабоване рішення для сучасної мобільної розробки.
Модель оцінювання модуляризації android-застосунків
Keywords: classification of approaches to Android application modularization implementing; modularization model; evaluation indicators for Android application modularization options; project cohesion and coherence; класифікація підходів до реалізації модуляризації Android-застосунків; модель модуляризації; показники оцінки варіантів модуляризації Android-додатків; зв'язність та узгодженість проекту